Factors associated with decreased compliance after on-site extracorporeal membrane oxygenation cannulation for acute respiratory distress syndrome: A retrospective, observational cohort study - Sylvain Le Pape; Florent Joly; François Arrivé; Jean-Pierre Frat; Maeva Rodriguez; Maïa Joos; Laura Marchasson; Mathilde Wairy; Arnaud W. Thille; Rémi Coudroy (Journal of Intensive Medicine, 2024)
Background: Extracorporeal membrane oxygenation (ECMO) for acute respiratory distress syndrome (ARDS) is systematically associated with decreased respiratory system compliance (CRS). It remains unclear whether transportation to the referral ECMO center, changes in ventilatory mode or settings to achieve ultra-protective ventilation, or the natural evolution of ARDS drives this change in respiratory mechanics. Herein, we assessed the precise moment when CRS decreases after ECMO cannulation and identified factors associated with decreased CRS. Methods: To rule out the effect of transportation and the different modes of ventilation on CRS, we conducted a retrospective, single-center, observational cohort study from January 2013 to May 2020, on 22 patients with severe ARDS requiring on-site ECMO and ventilated in pressure-controlled mode to achieve ultra-protective ventilation. CRS was assessed at different time points ranging from 12 h before ECMO cannulation to 72 h after ECMO cannulation. The primary outcome was the relative change in CRS between 3 h before and 3 h after ECMO cannulation. The secondary outcomes included variables associated with the relative changes in CRS within the first 3 h after ECMO cannulation and the relative changes in CRS at each time point. Results: CRS decreased within the first 3 h after ECMO cannulation (−28.3%, 95% confidence interval [CI]: −38.8 to −17.9, P<0.001), while the decrease was mild before and after these first 3 h after ECMO cannulation. To achieve ultra-protective ventilation, respiratory rate decreased in the mean by –13 breaths/min (95% CI: −15 to −11) and driving pressure by −8.3 cmH2O (95% CI: −11.2 to −5.3), resulting in decreased tidal volume by −3.3 mL/kg of predicted body weight (95% CI: −3.9 to −2.6) as compared to before ECMO cannulation (P <0.001 for all). Plateau pressure reduction, driving pressure reduction, and tidal volume reduction were significantly associated with decreased CRS after ECMO cannulation, whereas neither respiratory rate, positive end-expiratory pressure, inspired fraction of oxygen, fluid balance, nor mean airway pressure was associated with decreased CRS. Conclusions: Decreased driving pressure resulting in lower tidal volume to achieve ultra-protective ventilation after ECMO cannulation was associated with a marked decrease in CRS in ARDS patients with on-site ECMO cannulation.